Territorial tourism resilience in the COVID-19 summer - JuanAntonio Duro; Alejandro Perez-Laborda; Melchor Fernandez (Annals of Tourism Research Empirical Insights, 2022)
This paper quantitatively analyzes the resilience of tourism to COVID-19 and its territorial distribution in Spain, a global tourism power and one of the countries most affected by the pandemic. A first descriptive analysis of data from the summer of 2020 shows that: i) resilience was not homogeneously distributed across Spanish provinces; ii) the territorial concentration of tourism demand decreased due to the pandemic crisis; iii) the distribution of resilience was not consistent with standard indicators of tourism competitiveness. Econometric modeling shows that pre-pandemic domestic market specialization and population density explain most observed variability. Therefore, resilience was largely predetermined, so that the different policies adopted by some territories to attract domestic demand played a minor explanatory role.